Response to Selection for a High or a Low Sex Ratio in Wolbachia-infected Lines of Trichogramma cordubensis Subjected to High Temperature - Pintureau, B.; Bolland, P. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
Trichogramma cordubensis is an
egg parasitoid completely infected by endosymbiotic bacteria belonging to the Wolbachia genus and inducing the thelytokous mode of reproduction. Previous results showed that the thelytoky persistence at
high temperature is genetically variable. Experimental selection was performed to confirm these results
and to determine the possibilities of adaptation to the environment assuming cyclic bisexual reproduction. No selection was efficient and the genetic variability of the sex ratio at high temperature is probably lower than previously assumed. This reduces the adaptive possibilities in the studied Trichogramma
species. Установлено, что Trichogramma cordubensis - яйцевой паразит, характеризующийся наличием эндосимбионтных бактерий Wolbachia и телитокическим способом размножения. Отмечено, что устойчивость к высокой температуре у телитокических видов генетически варьирует. Проведена экспериментальная селекция линий с высоким и низким половым индексом для определения возможных адаптаций к условиям окружающей среды, вызывающим двуполый способ размножения. Установлено, что селекция выбранных линий была не эффективной. Генетически обусловленная изменчивость полового индекса при высокой температуре оказалась ниже, чем предполагалось. Отмечено, что это уменьшает адаптивные возможности T. cordubensis.